The binomial squares pattern is given by (a - b)^2 = a^2 - 2ab + b^2. Here, a = 8u^3 and b = 3.
First, calculate a^2, which is (8u^3)^2 = 64u^6.
Second, compute 2ab, which is 2*(8u^3)*3 = 48u^3.
Lastly, find b^2 where b = 3, so b^2 = 3^2 = 9.
According to the pattern, the expanded form of (8u^3 - 3)^2 is computed by adding the above results together.
Finally, combine all the results obtained: 64u^6 - 48u^3 + 9.
So, the answer to the question "What is the binomial squares pattern of (8u^3 - 3)^2" is a) 64u^6 - 48u^3 + 9.
Answer: a) 64u^6 - 48u^3 + 9